The ORF4b-encoded accessory proteins of Middle East respiratory syndrome coronavirus and two related bat coronaviruses localize to the nucleus and inhibit innate immune signalling - Matthews, Krystal L. (Society for General Microbiology, 2014)
The recently emerged Middle East respiratory syndrome coronavirus (MERS-CoV), a betacoronavirus, is associated with severe pneumonia and renal failure. The environmental origin of MERS-CoV is as yet unknown; however, its genome sequence is closely related to those of two bat coronaviruses, named BtCoV-HKU4 and BtCoV-HKU5, which were derived from Chinese bat samples. A hallmark of highly pathogenic respiratory viruses is their ability to evade the innate immune response of the host. CoV accessory proteins, for example those from severe acute respiratory syndrome CoV (SARS-CoV), have been shown to block innate antiviral signalling pathways. MERS-CoV, similar to SARS-CoV, has been shown to inhibit type I IFN induction in a variety of cell types in vitro. We therefore hypothesized that MERS-CoV and the phylogenetically related BtCoV-HKU4 and BtCoV-HKU5 may encode proteins with similar capabilities. In this study, we have demonstrated that the ORF4b-encoded accessory protein (p4b) of MERS-CoV, BtCoV-HKU4 and BtCoV-HKU5 may indeed facilitate innate immune evasion by inhibiting the type I IFN and NF-κB signalling pathways. We also analysed the subcellular localization of p4b from MERS-CoV, BtCoV-HKU4 and BtCoV-HKU5 and demonstrated that all are localized to the nucleus.